Comparison of Single and Dual Orifice Synthetic Jets for Flow Structure and Heat Transfer - Ahmed, Faisal; Azarifar, Mohammad; Ikhlaq, Muhammad; Arik, Mehmet (InterSociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems, 2024)
Synthetic jets have garnered considerable attention in electronics thermal management due to their notable attributes, including compactness, low energy consumption, cost-effectiveness, and user convenience. Numerous rigorous studies have delved into the characteristic parameters of both single-orifice and multiple-orifice synthetic jet devices to comprehend heat transfer and flow physics for a wide range of applications. This study focuses on investigating the heat transfer capability of a dual-orifice synthetic jet over a single-orifice synthetic jet to address space constraint. An SST k-ω turbulence model with a commercially available CFD software (ANSYS Fluent) was used to investigate the thermal and fluidic behavior of a single-orifice synthetic jet and a dual-orifice synthetic jet. The current study explored the effects of varying widths of two orifices and the spacing between them. By utilizing an identical cavity and equal excitation parameters, results indicate an approximate 4% additional reduction in the average temperature of the heated surface when employing a dual-orifice synthetic jet configuration. Moreover, the dual-orifice synthetic jet exhibited a 6% higher average heat transfer coefficient compared to a conventional synthetic jet, while the performances of the other two configurations of dual-orifice synthetic jets were surpassed by a single-orifice synthetic jet. These outcomes can be attributed to the variation of jet interactions introduced by different dual-orifice configurations.